2003
DOI: 10.1038/sj.ijo.0802198
|View full text |Cite
|
Sign up to set email alerts
|

Strength training for obesity prevention in midlife women

Abstract: OBJECTIVE:The primary goal of this study was to assess whether increases in fat-free mass (FFM) and decreases in total and percentage fat mass from 15 weeks of twice weekly supervised strength training would be maintained over 6 months of unsupervised exercise in a randomized controlled trial. DESIGN: In all, 60 women aged 30-50 y, body mass index between 20 and 35 kg/m 2 , were randomized to control or treatment groups. The treatment group performed twice-weekly supervised strength training followed by 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 38 publications
1
53
1
4
Order By: Relevance
“…Jakobsen et al were the only authors to report effect sizes for a portion of their results (23). For three publications effect sizes could not even be calculated retrospectively (25,28,30). The effect sizes we calculated are given with the individual results below.…”
Section: The Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Jakobsen et al were the only authors to report effect sizes for a portion of their results (23). For three publications effect sizes could not even be calculated retrospectively (25,28,30). The effect sizes we calculated are given with the individual results below.…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…After elimination of duplicates and scrutiny of study titles and abstracts, 68 articles remained for full-text analysis. Twelve publications fulfilled the selection criteria laid out in Table 1 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The commonest reasons for exclusion were the absence of sex-specific analysis and the lack of muscle strength measurement.…”
Section: Study Selectionmentioning
confidence: 99%
“…Schmitz et al (13) found that increases in LBM after a 15-week supervised strength-training program in middle-aged women could be maintained over 6 months through an unsupervised program in an exercise facility. In addition, the observation that muscle strength increases from a supervised resistance training program were maintained after 6 months of home-based training is consistent with recent findings in overweight middle-aged women (13). However, the finding that home-based training did not induce further strength gains from those observed during supervised training is most likely due to the reduced training volume during this period.…”
Section: Changes In Physiological Outcomesmentioning
confidence: 99%
“…20 -23 Second, adherence to exercise interventions is an issue for all populations and we have recently demonstrated the behavioral feasibility of twice-weekly weight training among midlife women who are not cancer survivors. 23 Finally, there is the potential that for breast cancer survivors, weight training might increase a sense of control over their lives during the 'watchful waiting' time frame between the end of active treatment and the 5-year mark postdiagnosis (e.g., psychological empowerment via physical strength increases).…”
mentioning
confidence: 99%